Memahami Pesan Teks Al-Hariiq Melalui Pendekatan Kontekstual dan Interteks dalam Kitab Qiroaturrosyidah - Muhammad Fauzan, Fatta; Susiawati, Wati; Nisa', Mauidlotun; Wildan Sahuri Ramdani, Ahmad; Rizqi Alif Syuhada', Mohammad (Green Publisher Indonesia, 2025)
Al-Hariiq in the Arabic context means fire, but in various social and cultural traditions, the term has a broader and symbolic meaning. Fires are not only understood as natural disasters, but also related to social, cultural, and spiritual phenomena in people's lives. In this context, al-Hariiq can reflect the tradition of land clearing with the slash and burn method by the Dayak people or the Sewu Ngewu ritual which is carried out to reject the army in Rakeda Village. This study aims to analyze the meaning of the text of al-Hariiq (fire) in the book Qira'at al-Rasyidah through contextual and intertextual approaches. Therefore, this research is important to examine how al-Hariiq is not only understood literally, but also in a deeper sense in accordance with local social and cultural dynamics. The contextual approach is used to understand al-Hariiq from a social and cultural point of view, while the intertextual approach traces the meaning through relationships with other texts, both in classical Islamic literature, Jahiliyah literature, and ethical philosophy. The story of al-Hariiq in the book Qira'at al-Rasyidah is analyzed to have similarities with the story of the Prophet Moses and the poet Zuhair bin Abi Salma, which highlights the value of heroism, responsibility, and social solidarity. In the context of ethical philosophy, the heroic actions in this story can also be attributed to the principles of consequentialism and deontology, which affirm the importance of performing moral actions without prioritizing personal gain. The results of the study show that the text of al-Hariiq in Qira'at al-Rasyidah has a deep meaning and reflects the values of responsibility, leadership, and heroism. This research is expected to contribute to enriching the understanding of Arabic literary texts, as well as providing insight into the relationship between texts and cultural contexts in the Islamic literary tradition.